2004
DOI: 10.1111/j.1365-2249.2004.02416.x
|View full text |Cite
|
Sign up to set email alerts
|

GAD65 antibody isotypes and epitope recognition during the prediabetic process in siblings of children with type I diabetes

Abstract: SUMMARYWe observed 42 initially non-diabetic siblings of affected children to characterize the humoral immune response to the 65 kDa isoform of glutamic acid decarboxylase (GAD65) in preclinical type I diabetes. During the observation period with a mean duration of 9·6 years 21 siblings progressed to type I diabetes. The humoral immune response to GAD65 was observed initially as a simultaneous response to the middle (M) and carboxy (C)-terminal regions of the GAD65 molecule in most cases, and if the response w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 38 publications
(58 reference statements)
3
31
0
Order By: Relevance
“…This series of events is poorly documented in spontaneously diabetic laboratory rodents, such as the NOD mouse or the BB rat, because neither animal has an autoantibody response of the character and magnitude that is observed in human type 1 diabetes. In humans, limited information about GAD65Ab isotypes at onset and in the prodromal period is available (7,8). The common assay used for the detection of autoantibodies is based on immunoprecipitation using Protein A Sepharose.…”
Section: Islet Cell Autoantibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This series of events is poorly documented in spontaneously diabetic laboratory rodents, such as the NOD mouse or the BB rat, because neither animal has an autoantibody response of the character and magnitude that is observed in human type 1 diabetes. In humans, limited information about GAD65Ab isotypes at onset and in the prodromal period is available (7,8). The common assay used for the detection of autoantibodies is based on immunoprecipitation using Protein A Sepharose.…”
Section: Islet Cell Autoantibodiesmentioning
confidence: 99%
“…Both multiple epitopes (7,8,70,75,78) and the reaction to the juxtamembrane region have been shown to be linked with progression to diabetes (7,78). In a longitudinal study of first-degree relatives, intramolecular epitope spreading was only observed among the progressors, while some of the nonprogressors showed a decrease in the number of epitopes bound (75).…”
Section: Daa Epitopesmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to GADAs, epitope spreading is frequent (17). Autoantibody reactivity is initially directed against epitopes within the middle region (residues 235-444) and the COOHterminal region (residues 440 -585) of GAD65, indicating that either a rapid spreading of reactivity or simultaneous immunization against distinct GAD65 regions can occur (17,18). Reactivity to NH 2 -terminal GAD65 epitopes in children is less common, weaker, and usually appears after that against central and COOH-terminal epitopes.…”
Section: Early Characteristics Of Islet Autoimmunitymentioning
confidence: 99%
“…GADA often appear in older age groups and are preferentially associated with HLA-DRB1*03 haplotypes [11]. The GADA level alone does not predict progression to diabetes, and controversial reports exist with respect to the relevance of GADA epitope reactivity to diabetes progression [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%